การกลายพันธุ์ Lactococcus lactis สายพันธุ์ MF2 เพื่อเพิ่มการสร้างไนซิน - มาลินี สิงห์โตทอง (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
Lactococcus lactis MF2 isolated from raw milk was capable of producing nisin. The bacteria was grown in MRS medium at 30ºC for 24 hours. Growth was measured as optical density at 600 nm and found that the 9th hour of incubation period is a mid-log phase that is suitable to be a starter for improving the strain. After 3 rounds of UV exposure at 254 nm for 60-80 sec and 3 rounds of 50 g/ml NTG treatment for 10-60 min, the highest producing strains designated as MU2NUN2 1, MU2NUN2 2 and MU2NUN2 3 gave nisin activity of 2,638.89, 2,265.45 and 2,564.23 IU/ml respectively or a 7-fold increase more than original strain that was able to produce nisin only 370.51 IU/ml. The strains showed their stability of nisin production after 5 rounds of consecutive subculture by giving approximately activities of 90.4, 87.24 and 85.29%, respectively. MU2NUN2 1 was subjected to media optimization by using 1% sucrose in MRS medium. The result showed that MU2NUN2 1 was able to produce nisin up to 4,303.09 IU/ml or a 1.67-fold increase.